Houses and domestic life in the Viking Age and medieval period: material perspectives from sagas and archaeology - Vidal, Teva (2013)
This thesis examines the representations of houses as physical structures in the Íslendingasögur with specific emphasis on the material aspect of housing culture in the Viking Age and medieval period, as well as the interactions between material culture and text. The Íslendingasögur were written in Iceland as of the thirteenth century, but look back onto the Viking Age (c. 800-1100 AD). Comparison with the archaeology of domestic space reveals that the house in the Íslendingasögur generally corresponds with medieval housing models, contemporary with the period of saga writing. However, there are also examples of structures which correspond to the models of the Viking Age. Descriptions of antiquated buildings are sometimes framed in statements that make explicit reference to the chronological separation between the Viking Age and the writer’s present time, suggesting a familiarity with the evolution of housing culture. Detailed analysis of buildings in the sagas reveals domestic space in its context of use, and demonstrates how the physical nature of the house and farm framed the productive and social activities that went on within. The materiality of domestic life has particular importance for the dispensing of hospitality. Demonstrations of domestic space in use also allow for a better understanding of the relationship between objects and language, and elucidate some difficulties in translation and academic usage both in archaeology and literary studies. Material culture can itself influence the processes of composition in oral/written narratives such as the sagas, by inspiring the formation of narrative episodes. The built environment can also provide a contextual framing for narratives, acting as a mnemonic device facilitating the preservation and transmission of saga narratives.